2014
DOI: 10.1039/c4cp01072h
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular pnicogen interactions in phosphorus and arsenic analogues of proton sponges

Abstract: A computational study of the intramolecular pnicogen bond in 1,8-bis-substituted naphthalene derivatives (ZXH and ZX2 with Z = P, As and X = H, F, Cl, and Br), structurally related to proton sponges, has been carried out. The aim of this paper is the study of their structural parameters, interaction energies and electronic properties such as electron density on the intramolecular interaction. The calculated geometrical parameters associated to the P···P interaction are in reasonably good agreement with the cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 113 publications
6
53
0
Order By: Relevance
“…The pnicogen bond is a Lewis acid-Lewis base interaction in which the Lewis acid is a group 15 element (N, P, As, or Sb) acting as an electron-pair acceptor. [13][14][15]. Pnicogen bonds were first described theoretically for model complexes [16,17], and subsequent studies confirmed the stabilizing nature of pnicogen interactions [18][19][20].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The pnicogen bond is a Lewis acid-Lewis base interaction in which the Lewis acid is a group 15 element (N, P, As, or Sb) acting as an electron-pair acceptor. [13][14][15]. Pnicogen bonds were first described theoretically for model complexes [16,17], and subsequent studies confirmed the stabilizing nature of pnicogen interactions [18][19][20].…”
Section: Introductionmentioning
confidence: 87%
“…For these calculations, the Ahlrichs [41] qzp basis set was placed on 13 C, 15 N, 17 O, and 19 F, and the qz2p basis set on 31 P, 35 Cl, and hydrogen-bonded 1 H atoms. The Dunning cc-pVDZ basis set was placed on all other 1 H atoms.…”
Section: Ab Initio Calculationsmentioning
confidence: 99%
“…[68,69] This basis set and functional have been applied previously to similar sorts of systems to good effect. [14,[33][34][35][70][71][72][73][74][75] Relativistic effects are expected to be most significant for atoms below the third row of the periodic table. Minima on each potential energy surface were assured by the absence of any negative frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…This level of theory is widely used in the literature http and provides accurate data for systems of this sort [15][16][17][18][19][20][21][22]. Interaction energies were partitioned into separate contributions by Symmetry Adapted Perturbation Theory (SAPT) [23,24] at the Hartree-Fock level with the same aug-cc-pVDZ basis set as implemented in the MOLPRO software [25].…”
Section: Methodsmentioning
confidence: 99%